Flowgraph Representation of Information System Using Rough Set Theory - Upadhyay, Niharika; Jain, Pragati (International Journal of Computer Sciences and Engineering, 2025)
Lot of work has been done to classify raw data, for e.g. Data Mining, Machine Learning etc. But in these approaches uncertainty is not focused. Thus in this we are trying to find accuracy when uncertainty is in raw data. The starting point of rough set theory is an information system In this paper, Rough Set Theory is applied on 9 different mobile brands. Survey is conducted where 334 participants were asked to evaluate these 9 brands on different parameters. Using this information, Decision table and Flow Graph will be created and will found accuracy and strength of same.